Upaya Guru IPS Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran IPS Kelas Vlll Di SMP Negeri 3 Kedungwaru Tulungagung - Wiwis Meike; Jani Jani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The background of this research is the lack of interest in student learning in the social studies subject of SMPN 3 Kedungwaru Tulungagung students, where there is an unpreparedness in learning and a lack of support from the school environment and family environment. The existence of this background requires attention and motivation to learn from the school and family so that students have a high interest in learning. The focus of the research in this thesis are: 1) What are the social studies teacher's efforts to increase student learning interest in social science subjects for class VIII students at SMP 3 Kedungwaru Tulungagung, 2) What are the supporting factors of social science teachers in increasing student learning interest in the subject social science lessons for class VIII students at SMP 3 Kedungwaru Tulungagung, and 3) What are the obstacles and solutions for IPS teachers in increasing student learning interest in social science subjects for class VIII students at SMPN 3 Kedungwaru Tulungagung. The objectives of this research are 1) to explain how social studies efforts increase students' interest in learning in social studies subjects for class VIII students at SMP Negeri 3 Kedungwaru Tulungagung, 2) to find out the supporting factors for social studies teachers in increasing interest in learning students in Social Sciences class VIII students at SMP Negri 3 Kedungwaru Tulungagung and 3) To find out social studies teacher's obstacles and solutions in increasing student learning interest in Social Sciences class VIII students at SMP Negri 3 Kedungwaru Tulungagung. In this study used a qualitative descriptive research method. Data obtained through interviews, observation and documentation. Observations were made to find out more closely about the object being researched, interviews were used to find out or find problems openly at SMP Negeri 3 Kedungwaru Tulungagung, while documentation was used to collect data by investigating existing documents and was a place for prepare a number of data so that researchers get the maximum information that can correctly describe the condition of the object under study. The results of this study indicate that the social studies teacher's efforts to increase student learning interest in social studies class VII at SMP Negri 3 Kedungwaru Tulunggung use 3 techniques, namely: Using learning methods such as lecture methods, group discussions, diagnostic assessments and skills training methods. The second uses the map learning model, collaborative learning, contextual learning. Third Use learning media such as: Interactive PPT, audio media, picture media and map and globe media. Supporting factors for Social Studies teachers in increasing student learning interest in Social Sciences subject class VIII SMP Negeri 3 Kedungwaru Tulungagung namely: School programs, Facilities that support student learning include: Libraries, Classrooms, Laboratories and Classrooms. Obstacles and Social studies teachers' solutions in increasing student learning interest in social science subjects for class VIII SMP Negeri 3 Kedungwaru Tulungagung can be grouped into two factors, namely internal factors and external factors. Internal factors come from within the students themselves, external factors consist of teachers, parents, peers. The solution to overcome these obstacles is to provide motivation.